Legal Certainty for The Reading and Signing of The Deed through Teleconferencing Media During The Covid 19 - Fahrul Ramadan; Reka Dewantara; M. Sudirman (Jurnal Hukum Prasada, 2022)
The Covid 19 pandemic hit Indonesia, in the hampering of notary work in carrying out their duties and positions due to the establishment of large-scale social restrictions (PSBB). As a result, many notaries closed their offices and conducted deed-making services using electronic technology and teleconferencing media. The problem studied in this study is 1) How is the validity of the reading and signing of deeds implemented through teleconferencing media during the Covid 19 pandemic? 2) How to reconceptualization of the arrangement of reading and signing of deeds implemented through teleconferencing media in realizing legal certainty during the Covid 19 pandemic period and after the Covid 19 pandemic period ends? This type of normative research uses statute approach, conceptual approach, and case approach. The results of this study were found: It needs to be written in the head of the deed regarding the reading of the deed using teleconferencing media, at the end of the deed is written a description of the use of digital signatures. At the time of reading the deed through the teleconference media Notary must be in his position for the creation of legal certainty where the deed is made. The need for the expansion of the meaning of the face in article 16 paragraph (1) letter m UUJN to face directly or use teleconferencing media. The meaning of signatures in UUJN needs to be expanded in meaning with digital signatures. The anatomy of the deed in Article 38 of UUJN needs to be changed in the form of deeds made through teleconferencing media and using digital signatures. Recommendations for the government need to harmonize article 5 paragraph (2) of the UU ITE with UUJN for the creation of legal certainty on deeds made by and before notaries digitally both the results and the process of making deeds